PENGARUH STRATEGI PROMOSI DAN KUALITAS PELAYANAN TERHADAP KEPUTUSAN PEMBELIAN PRODUK TABUNGAN EMAS PADA PT. PEGADAIAN CABANG PEKANBARU KOTA (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2022)
Company seeks closer to consumers through a variety of approaches such as various kinds of products, services, promotions, prizes and opening new branches and units are located easily accessible by the public. The strategy carried out by the company's management to maintain and increase the number of customers are get by the promotion and the service. The purposes of research to determine and analyze the effect of promotion strategy and quality service on purhasing decisions of gold saving product at PT. Pegadaian Branch of Pekanbaru Kota. This research is a descriptive study using quantitative approach, and the source of the data from this study coming from primary data obtained through the interview process and distributing questionnaires which were then tested statistically through the SPSS program and secondary data using product sales data for PT. Pegadaian Branch of Pekanbaru Kota from the year of 2016 - 2020. The analytical method used in this research is simple and multiple regression analysis, and through validity and reliability tests. In this study the results obtained are that the Promotion Strategy (X1) has a positive and significant effect on Purchase Decisions (Y), Quality Service (X2) has a positive and significant effect on Purchasing Decisions (Y), then the both of Promotion Strategy (X1) and Quality Service (X2) ) has a positive and significant effect on Purchase Decisions (Y)Keywords: Promotion Strategy, Quality Service and Purchasing Decision